Why Pilgrims Return: Experiential Support, Perceived Risk, and Motivation in Shaping Experiential Desire to Revisit - Yani, Ria Pitri (Universitas Tanjungpura, 2026)
This study examines the effects of experiential support, perceived risk, and motivation on pilgrims’ experiential desire to revisit, with religious ambience as a mediating variable in the Wali Songo pilgrimage tourism on Java Island, Indonesia. A quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM–PLS) was applied to data from 230 Muslim pilgrims who had visited the sites at least twice. The results show that experiential support, perceived risk, and motivation significantly influence both religious ambience and experiential desire. Religious ambience also has a significant positive effect on experiential desire and mediates the relationships between the antecedent variables and revisit desire. The study concludes that religious ambience plays a crucial role in strengthening pilgrims’ emotional and spiritual engagement, thereby enhancing their intention to revisit. These findings provide theoretical insight into experiential dynamics in religious tourism and practical implications for managing meaningful and sustainable pilgrimage experiences.